IDENTIFIKASI DEKULTURASI SEBAGAI TEORI PERUBAHAN KEBUDAYAAN DALAM MUSIK INDONESIA : KAJIAN PROSES PERUBAHAN REBANA MENJADI KASIDAH MODERN DI KOTA SEMARANG (Harmonia: Journal of Arts Research and Education, 2010)
At present, modern "kasidah" music has been known as a type of music that performs Moslem culture especially of people in Semarang. This type of music has become a phenomenon of musical art in the society in accordance with the development of other Moslem musical arts. Since there are many kinds of Moslem musical performances, and that they have similarities between one another, this study is meant to find out how the form of composition and the mode of performance of the music are presented, and also to identify the form of the music as a whole. This type of music wasn't formerly so popular in Semarang as it is today, but it has been developing gradually through a long process of acculturation. This music was considered to derive from Moslem musical tradition called "rebana" that has been acculturated into a modem "kasidah" music in Semarang. This study also highlights on how the acculturation went on, and on how the music gives benefit and function to the people. To reveal the problems mentioned above, the writer uses ethno musicological, anthropological, and historical approaches. The research method that the writer uses is qualitative-descriptive method as well as library research, observation, interview and documentation for research object. The target of the research is some musical groups of "kasidah" in Semarang and one of them is chosen as the sample of the research object. From the research, the writer found that the form of the musical composition consists of rhythm, melody, harmony, interval dynamics, expression, instruments, lyrics, and music analysis. Whereas, the modes of performance consist of stage production, costume, make-up, lighting, sound system, musical players, instruments, and times of performance. The benefits of the music for the society are corresponding with some aspects such as economical interest, social institution, aesthetic value, and language expression.Kata Kunci : dekulturasi, musik kasidah